Aortic smooth muscle TRPV4 channels regulate vasoconstriction in high salt-induced hypertension - Wen, Xin; Peng, Yidi; Peng, Yuefeng; Zhu, Yuzhong; Yu, Fan; Geng, Li; Zhou, Tingting; Wang, Xianfeng; Feng, Lei; Meng, Qingyou (Hypertension research, 2023)
Recent studies have focused on the contribution of vascular endothelial transient receptor potential vanilloid 4 (TRPV4) channels to hypertension. However, in hypertension, TRPV4 channels in vascular smooth muscle remain unexplored. In the present study, we performed wire myograph experiments in isolated aortas from endothelial cell specific TRPV4 channel knockout (TRPV4 ) mice to demonstrate that GSK1016790A (a specific TRPV4 channel agonist) triggered aortic smooth muscle-dependent contractions from mice on a normal-salt diet, and the contractions were enhanced in high-salt diet (HSD) mice. Intracellular Ca concentration ([Ca ] ) and Ca imaging assays showed that TRPV4-induced [Ca ] was significantly higher in aortic smooth muscle cells (ASMCs) from HSD-induced hypertensive mice, and application of an inositol trisphosphate receptor (IP R) inhibitor markedly attenuated TRPV4-induced [Ca ] . IP R2 expression was enhanced in ASMCs from HSD-induced hypertensive mice and the contractile response induced by TRPV4 was inhibited by the IP R inhibitor. Whole-transcriptome analysis by RNA-seq and western blot assays revealed the involvement of interferon regulatory factor 7 (IRF7) in TRPV4-IRF7-IP R2 signaling in HSD-induced hypertension. These results suggested that TRPV4 channels regulate smooth muscle-dependent contractions in high salt-induced hypertension, and this contraction involves increased [Ca ] , IP R2, and IRF7 activity. Our study revealed a considerable effect of TRPV4 channels in smooth muscle-dependent contraction in mice during high-salt induced hypertension.